2006
DOI: 10.1007/s10792-006-9004-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic outcome of scleral buckling surgery in primary rhegmatogenous retinal detachment

Abstract: Grade C(1) PVR and multiple breaks were found to be significant risk factors for anatomic failure in rhegmatogenous RD treated by conventional buckling surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
16
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
5
16
2
5
Order By: Relevance
“…Anatomic success rates were achieved with an increasing trend from 71.9% in group I to 87.5% in group II and 84.8% in group III, which is comparable to those of earlier studies (78–96%, depending on preoperative selection) [5,6,7,8,9]. This trend is also thought to be associated with surgical experience.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Anatomic success rates were achieved with an increasing trend from 71.9% in group I to 87.5% in group II and 84.8% in group III, which is comparable to those of earlier studies (78–96%, depending on preoperative selection) [5,6,7,8,9]. This trend is also thought to be associated with surgical experience.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, success rates for cases with multiple breaks increased from 43.8% in group A to 77.5% in group B, which is probably attributable to the acquired experience concerning multiple buckling in cases with multiple breaks. In the present study, success rates for multiple buckling were 33.3% in group A and 66.7% in group B. Afrashi et al [8] reported that multiple breaks were a significant risk factor for anatomic failure mentioning a success rate of 75.0% in the cases with multiple breaks, which corresponded to that of our group B.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite the fact that anatomical success rates have improved dramatically over the past century, with B90% or more of all RRDs successfully repaired with one or more operations, [1][2][3] postoperative visual acuity (VA) outcomes continue to be unpredictable in many patients.…”
Section: Introductionmentioning
confidence: 99%
“…With current surgical techniques, 90% or more of all retinal detachments can be successfully reattached with one or more operations (Wilkinson 2006), (Ho et al 2002), (Afrashi et al 2005). The two current -and, in some surgeons' opinion, competing -methods of treatment are scleral buckling with the intent to facilitate a reattachment and primary pars plana vitrectomy (PPV).…”
mentioning
confidence: 99%